Niño wrestles the world - Morales, Yuyi (Roaring Brook Press, 2013)
Lucha Libre champion Niño has no trouble fending off monstrous opponents, but when his little sisters awaken from their naps, he is in for a no-holds-barred wrestling match that will truly test his skills.